Dual role conflict, family support, and stress levels among nursing students in a recognition of prior learning program - Rachelita, Kezia; Sinaga, Mei Rianita Elfrida; Thojampa, Somsak (The Journal of Palembang Nursing Studies, 2025)
Background: Stress occurs when external demands exceed an individual’s coping resources. Nursing students enrolled in the Recognition of Prior Learning (RPL) program, who balance employment and academic responsibilities, are particularly vulnerable to dual role conflict, which may result in fatigue, pressure, and time management difficulties. Conversely, family support is a critical protective factor that helps individuals cope during challenging periods. Objective: This study examined the relationship between dual role conflict, family support, and stress levels among RPL nursing students. Methods: A quantitative, correlational, cross-sectional design was employed. The study included all 94 RPL nursing students through total sampling. Data were collected using the Dual Role Conflict Scale, the Perceived Social Support–Family (PSS-FA), and the Perceived Stress Scale-10 (PSS-10). Data analysis included frequency distribution, Somers’ d test, and ordinal logistic regression. Results: Of the 94 participants, most were female (75.5%), aged 26–53 years (58.5%), employed in hospitals (92.6%), and had 10–12 years of work experience (26.6%). Nearly half experienced low dual role conflict (44%), most reported good family support (93.6%), and the majority experienced moderate stress (62.8%). Multivariate analysis showed a significant relationship between dual role conflict and family support with stress levels (p < 0.001). The strength of the association, as indicated by Nagelkerke’s pseudo R², was 26.6%. Conclusions: Dual role conflict and family support were significantly associated with stress levels among RPL nursing students. Educational institutions should provide counseling services, stress management programs, and academic support tailored to the needs of working students. Further studies are recommended to explore additional factors influencing stress, such as peer support and individual coping strategies.